Quantitative biological response of two predators (Heteroptera: Notonectidae) in the larval control of Aedes aegypti (Diptera: Culicidae). (2021)
Predation is a biotic factor that influences the structure and functioning of ecosystems, its effect can be quantified through functional (FR) and numerical response in a successful-invasion context. We use FR to understand the coevolutionary relationships, and measured the biological response of the predators Notonecta peruviana and Buenoa fasciata in the control of fourth-stage larvae of Aedes aegypti (F1) at different densities (5, 10, 20, 35, 55 and 80 larvae / liter). Fasting predators (48 hours) were introduced to the test containers (one individual per species) and the FR, the number of preys consumed (Ne), the attack coefficient (a) and handling time (Th). N. peruviana and B. fasciata developed a type II FR in the consumption of larvae of Ae. aegypti (p ≤ 0.01), and occupied close handling times (Th) (t = –1.93; df = 12; p = 0.078). N. peruviana preyed (Ne) twice as many larvae of Ae. aegypti (p ≤ 0.05) and showed a higher attack coefficient (a) in relation to B. fasciata (t = 14.92; df = 12; p = 0.000). The predators N. peruviana and B. fasciata rapidly destabilized and consumed the preys. N. peruviana preyed twice as many larvae, attributable to the recent predator-prey effect compared to the possible coevolutionary adjustment between B. fasciata and Ae. aegypti. It would be important to consider the predator species in the vector control programs for aedine mosquitoes.